Analysis of Landslide Potential Based on Subsurface Lithology using Geoelectrical Method in Jatirejo, Wukirsari, Imogiri, Bantul, DIY - Hilma Lutfiana; Rial Dwi Martasari; Rahmawati Fitrianingtyas; Uli Ulfa; Mafrida Fayza Putri Hidayat; Khafidh Nur Aziz (Diponegoro University Semarang Indonesia, 2026)
Landslides are among the most recurrent natural hazards in Indonesia, particularly within the Special Region of Yogyakarta, where Bantul Regency is classified as a high-risk zone. Jatirejo Hamlet, situated in Wukirsari Village, Imogiri Subdistrict, is characterized by steep slope morphology, complex geological condition, and high rainfall intensity, all of which contribute to its high landslide susceptibility. This research aimed to characterize the subsurface lithology and identify potential slip surface in this area using the electrical resistivity method with Wenner array configuration. Geoelectrical surveys were conducted along four lines, each 225 meters in length, utilizing a Naniura NRD 300 HF resistivity meter. The inversion result indicated the presence of a low-resistivity layer (0.05-8.4 Ωm), interpreted as water-saturated clay, underlying more permeable layers and likely functioning as a slip plane. These conditions suggest a high potential for mass movement driven by gravitational forces and local geological structures, including the Opak Fault. The findings demonstrate that the Wenner array is effectively delineates subsurface slip surfaces and can serve as a valuable tool for informing hazard assessment and the development of mitigation strategies in landslide-prone regions such as Jatirejo.